2021
DOI: 10.1073/pnas.2026330118
|View full text |Cite
|
Sign up to set email alerts
|

Predicting transcriptional responses to cold stress across plant species

Abstract: Although genome-sequence assemblies are available for a growing number of plant species, gene-expression responses to stimuli have been cataloged for only a subset of these species. Many genes show altered transcription patterns in response to abiotic stresses. However, orthologous genes in related species often exhibit different responses to a given stress. Accordingly, data on the regulation of gene expression in one species are not reliable predictors of orthologous gene responses in a related species. Here… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 65 publications
1
55
1
Order By: Relevance
“…The genes Pgl_GLEAN_10034437, Pgl_GLEAN_10012611, Pgl_GLEAN_10027418, Pgl_GLEAN_ 10024973, and Pgl_GLEAN_10037615 were found coding for functions, such as Coatomer beta C-terminal region, Methyltransferase domain/Hen1 La-motif C-terminal domain, NHL domain containing protein, Coatomer epsilon subunit, and CCT motif, respectively. Furthermore, some of the genes, such as Pgl_GLEAN_10029543, Pgl_GLEAN_10034437, Pgl_GLEAN_10012611, Pgl_GLEAN_10027418, Pgl_GLEAN_ 10024973, Pgl_GLEAN_10037615, and Pgl_GLEAN_10032186 were also responsible for cold tolerance ( Meng et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes Pgl_GLEAN_10034437, Pgl_GLEAN_10012611, Pgl_GLEAN_10027418, Pgl_GLEAN_ 10024973, and Pgl_GLEAN_10037615 were found coding for functions, such as Coatomer beta C-terminal region, Methyltransferase domain/Hen1 La-motif C-terminal domain, NHL domain containing protein, Coatomer epsilon subunit, and CCT motif, respectively. Furthermore, some of the genes, such as Pgl_GLEAN_10029543, Pgl_GLEAN_10034437, Pgl_GLEAN_10012611, Pgl_GLEAN_10027418, Pgl_GLEAN_ 10024973, Pgl_GLEAN_10037615, and Pgl_GLEAN_10032186 were also responsible for cold tolerance ( Meng et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…One SNP was found closely associated with CP and nine SNPs were found associated with IVOMD (Table 5). The SNP for CP corresponded to the gene Pgl_GLEAN_10029543 were also responsible for cold tolerance (Meng et al, 2021).…”
Section: Gene Annotation For the Forage Quality Traitsmentioning
confidence: 99%
“…Transfer learning applications in plant breeding are just starting. For example, Meng et al (2021) used it for predicting transcriptional responses to cold stress across plant species; they found that models trained with data from one species successfully predicted which genes would respond to cold stress in other related species. Cross-species predictions remained accurate when training was performed in cold-sensitive species and predictions were performed in cold-tolerant species and vice versa.…”
Section: Why Can Research In DL Be Applied To Gs?mentioning
confidence: 99%
“…However, the total number of differentially expressed genes does not necessarily correlate with chilling tolerance or susceptibility (Marla et al., 2017). Recent work suggests that a trained model can predict genes that will transcriptionally respond to low temperature stress, even when the comparison species have different degrees of cold or chilling tolerance, which may prove useful in understanding low temperature stress responses across sorghum varieties and in other species (Meng et al., 2021).…”
Section: Challenges and Opportunities For Breeding And Engineering Chilling‐tolerant Sorghum Varietiesmentioning
confidence: 99%